On Dynamics of Certain Models via Generalized Conformable Fractional Derivative (Journal of Nonlinear Modeling and Analysis, 2025)
This paper deals with the generalized conformable fractional derivative and certain interesting properties which are not compatible with Riemann-Liouville and Caputo fractional derivatives. The newly defined derivative is more efficient than other conformable fractional derivatives and the nonlocal fractional derivatives from a time perspective. To justify the claim, we provide some direct applications, such as population growth, Newton’s body cooling, heat equation and susceptible-infected-removed models. Solutions obtained from models and comparison with respective previous data are demonstrated with the help of graphs or stems.
Keywords: Fractional derivative; SECH-fractional derivative; fractional population growth model; fractional body cooling model; fractional heat equation; SIR model